PREVENTIVE STRATEGIES FOR OCCUPATIONAL BURNOUT IN CORPORATE SETTINGS: A SYSTEMATIC LITERATURE REVIEW - Harisatun Najwa; Endang Dwiyanti (Lembaga Penelitian dan Terapan untuk Kesehatan Jiwa (Lenterakaji), 2026)
Background: Burnout represents a growing occupational health concern within corporate environments, manifesting in reduced productivity, absenteeism, and declining mental and physical well-being. Purpose: To synthesize evidence on preventive strategies for occupational burnout among corporate employees. Methods: A systematic literature review was conducted following PRISMA guidelines, using Google Scholar, ScienceDirect, ProQuest, and SpringerLink (2020–2025). Studies were identified using PICOS inclusion criteria and appraised with the Joanna Briggs Institute checklist. Results: Individual programs including Acceptance and Commitment Therapy based resilience training, mindfulness, Cognitive Behavioural Therapy tools, and workplace exercise reduced exhaustion while enhancing psychological flexibility and mental health literacy. Organizational approaches like security-providing leadership and psychoeducation with managerial consultation improved psychological safety. The strongest effects occurred when individual coping resources were supported by organizational structures. Although studies focused on corporate employees, differences in culture and context may limit generalization. Conclusion: Preventing burnout is most effective through combined individual and organisational measures. Sustainable, leadership-supported, technology-based programmes are recommended for long-term well-being and productivity. Abstrak Latar belakang: Burnout adalah masalah kesehatan kerja di korporasi, berdampak pada produktivitas, absensi, serta kesejahteraan mental dan fisik. Tujuan: Mensintesis bukti terkini strategi pencegahan burnout pada karyawan korporasi. Metode: Penelitian menggunakan Systematic Literature Review (SLR) berdasarkan pedoman PRISMA melalui Google Scholar, ScienceDirect, ProQuest, dan SpringerLink (2020–2025). Berdasarkan kriteria PICOS, studi memenuhi syarat dipilih dan dinilai menggunakan daftar tilik JBI. Hasil: Beragam intervensi menunjukkan manfaat. Program individu seperti pelatihan resiliensi berbasis Acceptance and Commitment Therapy, mindfulness, alat kreatif berbasis Cognitive Behavioural Therapy menurunkan burnout, meningkatkan fleksibilitas psikologis, efektivitas profesional, dan literasi kesehatan mental. Pendekatan organisasi seperti kepemimpinan yang memberi rasa aman dan psikoedukasi terpadu dengan konsultasi manajerial memperkuat keselamatan psikologis dan dukungan kerja. Efek terbaik muncul saat sumber daya individu mendapat dukungan organisasi. Meskipun studi berfokus pada karyawan korporasi, perbedaan budaya, durasi intervensi, dan konteks perusahaan dapat membatasi generalisasi temuan. Kesimpulan: Pencegahan burnout efektif melalui integrasi pendekatan individu dan organisasi. Program berkelanjutan yang didukung kepemimpinan dan teknologi direkomendasikan untuk kesejahteraan dan produktivitas jangka panjang.